2015
DOI: 10.3109/00365513.2014.993691
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis indexes for biochemical tests and immunoassays on Roche analyzers: Determination of allowable interference limits according to different calculation methods

Abstract: This study proposes new HI based on different allowable limits, and can therefore serve as a starting point for future harmonization of hemolysis interference evaluation needed in routine laboratory practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 17 publications
4
24
2
1
Order By: Relevance
“…In our study, though the hemolysis interference on biochemistry analytes was dependent on the analyzer system, the interference on CK, AST, LDH, and K was consistent with former studies using the Cobas 6000 c501 analyzer or Roche analyzers . This confirmed that a common mechanism underlies the observed hemolysis interference.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, though the hemolysis interference on biochemistry analytes was dependent on the analyzer system, the interference on CK, AST, LDH, and K was consistent with former studies using the Cobas 6000 c501 analyzer or Roche analyzers . This confirmed that a common mechanism underlies the observed hemolysis interference.…”
Section: Discussionsupporting
confidence: 92%
“…Hemolysis index (HI) generated by analyzers is an effective tool to counteract the hemolysis challenge, as it can standardize the process of identifying hemolytic specimens and estimate the hemolysis interferences quantitatively . Even though it was reported that the hemolysis index (HI) was accurate and highly reproducible among different platforms and laboratories, determining the HI threshold is the key to identify hemolytic effects.…”
Section: Introductionmentioning
confidence: 99%
“…change limit [ACL] [3,26]), as well as the arbitrary 10% cut-off point commonly used by manufacturers and laboratories [8,27,28]. Analytical test results from hemolyzed samples have also previously been reported heterogeneously.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 3.5% of blood samples arriving for biochemical testing present with haemolysis [31,32], which represents a source of interference with analyte determination. To compensate for this, haemolysis indexes (HI) have been established, but allowable limits of haemoglobin are not uniform, which introduces variability into analyte determination [33]. Clearly, it is important to improve coagulability and at the same time minimise haemolysis, which we have been able to do using OsPA addition to blood collection tubes.…”
Section: Discussionmentioning
confidence: 99%